Checkpointing Techniques in Distributed Systems: A Synopsis of Diverse Strategies Over the Last Decades - Goulart, Henrique; Franco, Álvaro; Mendizabal, Odorico (Anais do Workshop de Testes e Tolerância a Falhas (WTF); 2023: Anais do XXIV Workshop de Testes e Tolerância a FalhasDO - 10.5753/wtf.2023.785, 2023)
This paper concisely reviews checkpointing techniques in distributed systems, focusing on various aspects such as coordinated and uncoordinated checkpointing, incremental checkpoints, fuzzy checkpoints, adaptive checkpoint intervals, and kernel-based and user-space checkpoints. The review highlights interesting points, outlines how each checkpoint approach works, and discusses their advantages and drawbacks. It also provides a brief overview of the adoption of checkpoints in different contexts in distributed computing, including Database Management Systems (DBMS), State Machine Replication (SMR), and High-Performance Computing (HPC) environments. Additionally, the paper briefly explores the application of checkpointing strategies in modern cloud and container environments, discussing their role in live migration and application state management. The review offers valuable insights into their adoption and application across various distributed computing contexts by summarizing the historical development, advances, and challenges in checkpointing techniques.